The History of the Arts Council of Northern Ireland, 1943-2016 Between the State and the Arts - Cuny, Lara. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book presents the history of the Council for the Encouragement of Music and the Arts (CEMA) in Northern Ireland from its conception in 1943, and its successor organisation, the Arts Council of Northern Ireland (ACNI). Exploring the political and social impact of cultural policy in Northern Ireland, the book illustrates how the arts developed during the twentieth century and sheds light on the relationship between politics and culture. The author takes a closer look at the responsibilities of ACNI, and examines its interaction with the unionist government, which sought to influence how the organisation distributed its grants. Spanning the outbreak of the Troubles in the 1960s and the Peace Process in the 1990s, the ACNI evolved through a period of conflict and change, and therefore this book argues that there was an undeniable link between the changing political environment and the management of the arts in Northern Ireland. The arm's length principle is analysed in relation to ACNI, examining the influence that the state had upon its management and governance. Offering a unique historical overview of the arts in Northern Ireland, this interdisciplinary book fills a gap in Irish history and presents insights into cultural policy, conflict resolution and political history. Lara Cuny is Associate Professor at Aix-Marseille University, France. Previously she taught classes on Irish and British history at Sorbonne Nouvelle University, Paris.
Chapter 1. Introduction -- Part I. The Council for the Encouragement of Music and the Arts: From a Temporary Wartime Measure to a Permanent Institution, 1939-1951 -- Chapter 2. Arts and Culture in Northern Ireland before the Second World War -- Chapter 3. Creating the Council for the Encouragement of Music and the Arts -- Chapter 4. Establishing the Council for the Encouragement of Music and the Arts in the Northern Irish Political and Cultural Landscape -- Part II. The Evolution of the Council for the Encouragement of Music and the Arts: Politics, Culture and the Arts, 1950s-1960s -- Chapter 5. The Artistic Policy of the Arts Council: Educating the People -- Chapter 6. Politics, Sectarianism and the Creation of the Arts Council of Northern Ireland -- Chapter 7. A Regionalist Agenda in Northern Ireland -- Chapter 8. 1968-1972, A Transition -- Part III. Artistic Policy in a Violent Political Context: 1970s-1990s -- Chapter 9. In Times of War: A New Role for the Arts -- Chapter 10. The Isolationism of the Arts Council of Northern Ireland -- Chapter 11. Community Arts and their Development in Northern Ireland -- Chapter 12. The Arts Council of Northern Ireland and the Peace Process -- Part IV. The Arts Council's Integration into Northern Irish Cultural Policy: 1998-2016 -- Chapter 13. A New Institutional Framework -- Chapter 14. The Government and the Economic Potential of the Arts -- Chapter 15. The Arts Council of Northern Ireland: A Contested Development Agency -- Chapter 16. Conclusion.
Keywords: Great Britain-History.; History, Modern; Civilization-History.; Social history; World politics; History of Britain and Ireland; Modern History; Cultural History; Social History; Political History